Separation of Mupirocin by Normal Phase Liquid Chromatography (NPLC) - Patel, Jalpa; Desai, Gaurav; Upadhya, Archana (Separation science and technology, 2014)
Mupirocin is an antibiotic from Pseudomonas fluorescens used topically against Staphylococci infections. There are many patented strategies which are proposed for separation of the antibiotic from the fermentation broth comprising of liquid-liquid extraction and hydrophobic chromatography. The paper demonstrates the use of native silica, as used in flash chromatography, as adsorbent for normal phase liquid chromatography of mupirocin. Mobile phase for elution was acidified n-hexane: ethyl acetate (10/90 v/v). The method achieved a yield of 66% relative to the mupirocin source and a concentration factor of 13. Anti-microbial assays, high performance liquid chromatography and Fourier transform infrared spectroscopy has been used to confirm the identity of the antibiotic after chromatographic separation. An alternative route to isolation of mupirocin using the polar sorbent has been suggested.